Current Practices in Information Systems Development Tools and Techniques - Ku Mahamud, Ku Ruhana; Othman, Nafishah; Md. Norwawi, Norita (Malaysian Journal of Computer Science, 1997)
The study examines the current practices in information systems development practices among Malaysian information systems managers and system analysts. Technical, organisational and intrinsic facets of information systems development process are assessed. Results indicated that most information systems departments are well-established within their organisations having a close link to top management and majority of the respondents have formal tertiary education in computer science or management information system. The study also indicates that 4GLs, data flow diagrams, data dictionaries and system flowcharts are the most familiar and widely used system development tools. CASE tools are used by all respondents especially for the analysis and design, implementation and project management activities. Majority of the respondents indicate that microcomputers are used extensively and most applications were developed using SQL and COBOL.